WAYS TO INCREASE EFFICIENCY AND STABILITY INDICATORS OF FOREIGN INVESTMENT PROJECTS - Amonov Azizbek Shavkat o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2023)
Foreign investment projects are important contributors to the economic growth of a country. They are a way for companies to expand their business to other parts of the world and for governments to attract foreign capital and technology to their countries. However, not all foreign investment projects are successful, and many fail to meet their efficiency and stability indicators. In this article, we will discuss ways to increase the efficiency and stability indicators of foreign investment projects.